Hydropower and Dams (H&D) : Strengthening Climate-Informed Project Design - World Bank (Washington, DC, 2022)
This learning note is the second of a 4-note-series developed by the Water Global Practice (GP) Climate Change Team to highlight successful examples of water operations that support climate change–related activities and provide useful lessons and recommendations for project design.